Synthesis of 2, 5-furandicarboxylic acid-based biodegradable copolyesters with excellent gas barrier properties composed of various aliphatic diols. (5th December 2022) - Wang, Qianfeng; Wang, Jinggang; Dong, Yunxiao; Zhang, Xiaoqin; Hu, Han; OYoung, Lionel; Hu, Di; Zhu, Jin
Graphical abstract: Synthesis of 2, 5-furandicarboxylic acid-based biodegradable copolyesters with excellent gas barrier properties composed of various aliphatic diols. Highlights: Bio-based biodegradable polyesters. Effect of the segmental lengths. 2, 5-Furandicarboxylic acid. Various aliphatic diols. Good gas barrier properties. Abstract: Copolyesters based on 2, 5-furandicarboxylic acid (FDCA) have attracted particular attention due to their outstanding gas barrier properties and biodegradability compared with commodity degradable polymers. This study provides the first comprehensive assessment of the effect of the segmental lengths of aliphatic diols on the properties of FDCA-based copolyesters. A series of poly(alkylene adipate- co -furanoate) (PAAF) copolyesters comprised of different aliphatic diols were prepared via melt polycondensation reaction and their comprehensive properties, including thermal properties, mechanical properties, gas barrier properties, degradability, and antibacterial activities were thoroughly investigated. NMR and GPC results confirm the successful synthesis of high-molecular-weight random copolyesters (their Mw varies from 67, 500 to 126, 500 g·mol −1 ). The glass transition temperatures ( Tg ) of PAAFs decreases with increasing diol segmental lengths whereas a zig-zag variation in the melting temperatures ( Tm ) is observed due to the odd–even effect. All PAAFs exhibit good ductility and excellent mechanical properties with tensile moduli between 27 and 102 MPa. The gas barrier performances of PAAFs are 2.1 to 13.4 folds for O2 and 2.4 to 13.6 folds for CO2 better than those of poly(butylene adipate- co -terephthalate) (PBAT), respectively. All PAAFs can be rapidly biodegraded within 25 days under enzymatic hydrolysis conditions.